On avoiding of spurious mesh sensitivity in numerical analysis of plastic strain localization - Łodygowski, Tomasz (Computer Assisted Methods in Engineering and Science, 2023)
The successful numerical analysis of plastic strain localization phenomena in ductile and brittle materials requires the fulfillment of several conditions in accordance with the formulation of the initial boundary value problem (IBVP). Sometimes ·it is necessary to use the regularization techniques which result in well-posed ness of IBVPs. Then, there are several possibilities of introducing an internal length scale. If specific conditions are met, the results obtained in the numerical calculations are free of unexpected mesh sensitivity. In the paper the dynamical boundary values are studied. The rate-dependent regularized models of two materials are presented and used to solve practical engineering problems. The mathematical background which could be used to prove the well-posedness of IBVP as well as the physical arguments are discussed.